Pengaruh Pencucian Luka Dengan Rebusan Daun Sirih Merah Terhadap Penyembuhan Luka Dehiscence Pasien Diabetes Melitus - Rini Andri Yani; Dwi Astuti; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Diabetes mellitus is a chronic disease which can be characterized by the presence of blood glucose levels that exceed normal values. Diabetic gangrene is tissue necrosis in the peripheral parts of the body due to diabetes mellitus. Washing red betel leaves with 0.9% NaCl is more effective because red betel leaves contain alkaloid and flavonoid active substances. Purpose: to determine the effect of treating wounds with red betel leaf decoction on gangrenous wound healing in patients with diabetes mellitus. Method: This case study uses a descriptive method. Results: Treatment using red betel leaf decoction for 8 days obtained the result that the size of the wound was at score 1. Depth was still at stage 2, edges of the wound were at score 2, there were no caves, no exudate type, skin color around the wound changed to score 1 , The tissue that is edematous is still the same as before, which is in score 1. The tissue that is granulated occurs with 100% granulation light. Epithelialization has changed, which is on a score of 2. Conclusion: The results of the case study show that giving red betel leaf decoction accelerates the wound healing process in patients and is expected to avoid triggering factors for the occurrence of complications of gangrenous wounds in diabetes mellitus.